Reuse of Immobilized Weissella cibaria PN3 for Long-Term Production of Both Extracellular and Cell-Bound Glycolipid Biosurfactants - Subsanguan, Tipsuda; Khondee, Nichakorn; Nawavimarn, Parisarin; Rongsayamanont, Witchaya; Chen, Chien-Yen; Luepromchai, Ekawan (Frontiers in Bioengineering and Biotechnology, 2020)
Lactic acid bacteria (LABs) are generally recognized as safe (GRAS), and therefore, LAB biosurfactants are beneficial with negligible negative impacts. This study aims to maintain the biosurfactant producing activity of an LAB strain, Weissella cibaria PN3, by immobilizing the bacterial cells on a commercial porous carrier. For biosurfactant production, 2% soybean oil was used as the carbon source. After 72 h, immobilized cells were reused by replacing production medium. The extracellular and cell-bound biosurfactants were extracted from the resulting cell-free broth and cell pellets, respectively. SEM images of used immobilizing carriers showed increased surface roughness and clogged pores over time. Thus, the immobilizing carriers were washed in PBS buffer (pH 8.0) before reuse. To maintain biosurfactant production activity, immobilized cells were reactivated every 3 production cycles by incubating the washed immobilizing carriers in LB medium for 48 h. The maximum yields of purified extracellular (1.46 g/L) and cell-bound biosurfactants (1.99 g/L) were achieved in the 4th production cycle. The repeated biosurfactant production of 9 cycles were completed within 1 month, while only 2 g of immobilized cells/L were applied. The extracellular and cell-bound biosurfactants had comparable surface tensions (31 – 33 mN/m); however, their CMC values were different (1.6 and 3.2 g/L, respectively). Both biosurfactants had moderate oil displacement efficiency with crude oil samples but formed emulsions well with gasoline, diesel, and lavender, lemongrass and coconut oils. The results suggested that the biosurfactants were relatively hydrophilic. In addition, the mixing of both biosurfactants showed a synergistic effect, as seen from the increased emulsifying activity with palm, soybean and crude oils. The biosurfactants at 10 – 16 mg/mL showed antimicrobial activity towards some bacteria and yeast but not filamentous fungi. The molecular structures of these biosurfactants were characterized by FTIR as different glycolipid congeners. The biosurfactant production process by immobilized Weissella cibaria PN3 cells was relatively cheap given that two types of biosurfactants were simultaneously produced and no new inoculum was required. The acquired glycolipid biosurfactants have high potential to be used separately or as mixed biosurfactants in various products, such as cleaning agents, food-grade emulsifiers and cosmetic products.